Uma análise retórica de disposições informativas, interrogativas e declarativas em Tawjeeh al-Qira’at al-Mutawatirah - Abdelgelil, Mohamed Fathy Mohamed; Abubakar, Muhammad Habib; Hassan, Isyaku (Revista EntreLinguas, 2022)
Research into Al-Qira’at al-Mutawtirah (authentic modes of recitation) is very limited. This paper, therefore, aims to explore the rhetoric of al-Qira’at al-Mutawtirah in light of Arabic rhetorical manifestations. Such manifestations include informative, interrogative, and declarative utterances. The researchers employed an analytical approach to analyze the instances of selected al-Qira’at al-Mutawtirah in the Quran, whereby such utterances were carefully examined. The study revealed that the rhetoric of al-Qira’at al-Mutawtirah manifests in their meanings. The meanings of Qira’at can be deepened when we attempt to figure out their underlying rhetorical manifestations. Additionally, the hidden meanings of Qira’at can be discovered when we combine the meanings of Qira’at. It was envisaged that this study could advance our knowledge regarding the role of different modes of citations in understanding the meanings of the Quran.